Survival outcome of lobar or segmental transcatheter arterial embolization with ethanol-lipiodol mixture in treating hepatocellular carcinoma - Cheung, Yun-Chung (World J Gastroenterol, 2005)
AIM: To evaluate the clinical outcome and cost-effectiveness of transcatheter arterial ethanol-lipiodol embolotherapy on hepatocellular carcinoma (HCC). METHODS: One hundred patients with HCC who were treated only by lobar or segmental transarterial embolization (TAE) with ethanol-lipiodol mixture were enrolled in this study. The 1st- and 2nd-year survival rates were analyzed to evaluate the feasibility of its method. These outcomes of our patients were individually correlated to the Child-Pugh classification and the computed tomographic features of HCC. RESULTS: The overall 1st- and 2nd-year survival rates were 72% and 46%, respectively. The patients were classified into three groups according to their liver function status: 68 patients as Child-Pugh class A, 26 as Child B, and 6 as Child C. Child A had better survival rate than the Child B and/or C. The 1st-year survival rates of patients with Child A-C were 84%, 50%, and 33.3% respectively and the 2nd-year survival rates were 55.5%, 28.5%, and 33.3%, respectively. According to the computed tomographic features, solitary HCC with maximum diameter less than 5 cm had the best outcome with the 1st-year survival rate of 100% and the 2nd-year survival rate of 71.4%, while solitary HCC with maximum diameter over 5 cm and multiple HCC had the 1st-year survival rates of 75% and 63.7%, respectively, and the 2nd-year survival rates of 33.3% and 44.4%, respectively. Only one patient was complicated with abscess formation and was cured with antibiotic therapy. No mortality resulted from the procedures performed. CONCLUSION: TAE with ethanol-lipiodol mixture is an economic, safe and feasible method for treating HCC, especially for the patients with smaller solitary HCC or with liver function status of Child-Pugh class A.